Y-Stent Rescue Technique for Failed Thrombectomy in Patients With Large Vessel Occlusion: A Case Series and Pooled Analysis - Li, Zifu; Liu, Peng; Zhang, Lei; Zhang, Yongwei; Fang, Yibin; Xing, Pengfei; Huang, Qinghai; Yang, Pengfei; Liu, Jianmin (Frontiers in Neurology, 2020)
Objective Y-stent thrombectomy is a recent rescue technique for failed thrombectomy in patients with emergent large vessel occlusion. We presented case series of using Y-stent rescue technique at different sites and investigate its feasibility and safety through pooled analysis of collected case report or series. Methods Twenty-eight cases were screened from stroke databank who underwent thrombectomy between January 2015 and June 2019. Clinical, procedural and follow-up data were investigated and pooled analysis of published literature was analyzed. Results The occlusion sites include carotid terminus in 14 patients; siphon segment in 3; middle cerebral artery (MCA) in 4; basilar terminus in 7. The overall recanalization rate reached 85.7% (arterial occlusive lesion score 2-3); and final reperfusion rate 85.7% (modified Thrombolysis in Cerebral Infarction 2b-3). After literature review, totally, 52 cases were included. Good clinical outcome was achieved in 26 (50%) and mortality in 7 (17.3%). There is no significant difference on the SAH complication at different sites. Literature review shows no difference between each site in the reperfusion and complication rate. Conclusion Our case series results suggest that high recanalization rate can be effectively achieved with Y-stent rescue technique for patients with refractory emergent large vessel occlusion. The safety of using this technique at different sites needs further investigation for patients.